EVALUASI STABILITAS FISIK DAN PROFIL DIFUSI SEDIAAN GEL (MINYAK ZAITUN) - A. Mumtihanah Mursyid (Jurnal Fitofarmaka Indonesia, 2017)
Olive oil contains vitamin E which is a natural antioxidant that is effective to prevent premature aging. The aims of the research was to obtained the most stable gel formulation of polyfloral honey phamaceutically.Physical stability evaluation carried out to in which the parameters were organoleptic, viscosity measurement, homogeneity, spreedability, pH, and flowing type, at 5oC and 35oC for 12 hours on each temperature for 10 cycles.Organoleptic assay showed that there was on change in color, odor, and concistency of all formula. Based on statistic analyses by Randomized design exhibited a significant change during storage. Homogeneity test showed that all formula posses even particle distribution. Spreedability test showed that all formula there were changes in viscosity. Based on rheogram exhibited thixotrophy-plastic flow type. From physical evaluation obtained formula B of gel was the must stable (Base gel of HEC). Based on release of active substances formula B of gel (Base gel of HEC) showed the highest release of active substances.